(untitled) - Hanreddy, Jami Ferrer (New York, 1996)
The Mosaic one program consists four texts and a variety of supplemental materials for intermediate to high-intermediate students seeking to improve their English language skills.
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc